A Meta-Analysis of Probiotics for the Treatment of Allergic Airway Diseases in Children and Adolescents. Issue 4 (July 2022) - Chen, Na; Liu, Fang; Gao, Qiang; Wang, Rui; Zhang, Lei; Li, Youwei
Background: Allergic airway disease is a chronic airway allergic inflammatory disease including allergic rhinitis (AR) and allergic asthma which is common in children and adolescents. Recently the probiotics has been becoming a supplementary or alternative therapy to allergic diseases, however the effect of them has not been clearly established. Objective: The purpose of the present meta-analysis was to evaluate the effectiveness of probiotics on allergic airway disease including AR and allergic asthma in children and adolescents. Methods: We performed a comprehensive search on PubMed, Cochrane Library, EMBASE for relevant publications from 1 Jan 2000 to 1 July 2021. Physical examinations, Pediatric Rhinoconjunctivitis Quality of Life Questionnaires (PRQLQs), Total Nasal Symptom Score (TNSS), Nasal or Eye Symptom Score (NSS or ESS), serum allergen-specific IgE, and eosinophil were used as evaluating indicators for AR and allergic asthma in children and adolescents. The meta-analysis was performed using Review Manager (RevMan, Version 5.3). Results: 15 randomized controlled trials (RCTs) with a total of 1388 participants were included for the meta-analysis. Among them, 729 patients treated with probiotics served as the probiotics group, and 659 patients with placebo as control group. Significantly greater reduction in PRQLQs from baseline to endpoint (SMD = −2.57, 95% CI [ − 4.66, −0.48] P < 0.01), NSS (SMD = −1.43, 95% CI [ − 1.63,  − 1.23], P < 0.01) and ESS (total MD = −1.67, 95% CI [ − 1.79,  − 1.55], P < 0.01) were observed in probiotics group compared to control group. Probiotics have no significant effect to serum IgE and eosinophils (P > 0.01). Conclusion: The results of this meta-analysis indicated that probiotics treatment may reduce PRQLQs, NSS, ESS in patients with allergic airway disease. More research involving the mechanism of probiotics are needed to clarify the role of probiotics in AR and allergic asthma in children and adolescents.